Why Do Sealers Seal? Cultural versus Economic Reasons for Participating in the Newfoundland Seal Hunt - Wright, Guy (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1981)
The protest against the Newfoundland seal hunt has helped to put the hunt in a position of prominence as an important symbol of Newfoundland identity. This has given the sealers an extra set of motivations for participating in it, beyond economics. However, the sealers are reticent about revealing the non-economic motives for sealing. This paper proffers certain social and cultural motives and explains the methodology necessary to discover them.